The prognostic value of sleep patterns in disorders of consciousness in the sub-acute phase. Issue 2 (February 2016) - Arnaldi, Dario; Terzaghi, Michele; Cremascoli, Riccardo; De Carli, Fabrizio; Maggioni, Giorgio; Pistarini, Caterina; Nobili, Flavio; Moglia, Arrigo; Manni, Raffaele
Highlights: Regular sleep structure is a good predictor of clinical outcome in sub-acute DOC patients. Regular sleep structure is stronger than other known prognostic factors of DOC outcome. Visual-quantitative sleep analysis is helpful in the prognostic evaluation of DOCs. Abstract: Objective: This study aimed to evaluate, through polysomnographic analysis, the prognostic value of sleep patterns, compared to other prognostic factors, in patients with disorders of consciousness (DOCs) in the sub-acute phase. Methods: Twenty-seven patients underwent 24-h polysomnography and clinical evaluation 3.5 ± 2 months after brain injury. Their clinical outcome was assessed 18.5 ± 9.9 months later. Polysomnographic recordings were evaluated using visual and quantitative indexes. A general linear model was applied to identify features able to predict clinical outcome. Clinical status at follow-up was analysed as a function of the baseline clinical status, the interval between brain injury and follow-up evaluation, patient age and gender, the aetiology of the injury, the lesion site, and visual and quantitative sleep indexes. Results: A better clinical outcome was predicted by a visual index indicating the presence of sleep integrity ( p  = 0.0006), a better baseline clinical status ( p  = 0.014), and younger age ( p  = 0.031). Addition of the quantitative sleep index strengthened the prediction. Conclusions: More structured sleep emerged as a valuable predictor of a positive clinical outcome in sub-acute DOC patients, even stronger than established predictors (e.g. age and baseline clinical condition). Significance: Both visual and quantitative sleep evaluation could be helpful in predicting clinical outcome in sub-acute DOCs.